A study on the heat behaviour of PEM, prepared by incorporation of crosslinked sulfonated polystyrene in the blend of PVdF-co-HFP/Nafion, for its high temperature application in DMFC. (March 2015) - Kumar, Piyush; Jagwani, S.K.; Kundu, Patit Paban
Abstract: Sulfonated polystyrene within the blend of PVdF- co -HFP/Nafion has shown promising PEM characteristics in terms of improved water uptake/swelling, proton conductivity, and output current/maximum power densities compared to Nafion-117. In addition, the semi-IPN membrane exhibited good oxidative stability, comparable ion-exchange capacity and methanol permeability. These inspiring results have led us to analyze the high temperature performance and structure–property relationship of this semi-IPN/blend membrane. We have utilized the techniques of FT-IR spectroscopy, scanning electron microscopy, AC impedance, tensile, and differential scanning calorimetry for this purpose. In addition, we have studied the effect of temperature on the cell performance of this prospective PEM. The membrane S-20 showed comparable tensile strength to that of Nafion and good thermal stability. In addition, it was found that impregnation of SS within the blend can effectively reduce the anhydrous condition of the membrane while operating at higher temperatures, and thereby, leading to higher electrical performance.